Medical authority and Englishwomen's herbal texts: 1550 - 1650 - Laroche, Rebecca (Literary and scientific cultures of early modernity, 2009)
"This manlike worke of herbes" : gender and the English herbal -- Inscriptions in herbal texts and the location of medical authority -- Gentlewomen's herbal readings and the absent-present physicians -- Isabella Whitney's herbs : print medical texts and London satire